Risk Analysis H2S And NH3 Exposure to Local Community Around Benowo Landfill Surabaya - Farha Ariba Imandini; Khambali; Ngadino; Rachmaniyah; Teguh Mubawadi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Final waste processing in Indonesia adopts a landfill system. The Benowo landfill employs this system, which has a weakness in producing H2S and NH3 gases. The objective of this study was to assess the level of public health risk present in the Benowo landfill environment. The study design used was quantitative descriptive with a cross-sectional approach. The sample size consisted of 93 housewives selected using simple random sampling techniques, and gas measurements were conducted at two locations. The data analysis methods employed were univariate analysis and ARKL. The findings of this research demonstrated that the level of hydrogen sulfide (H2S) gas measured 0.02 ppm, while the concentration of ammonia (NH3) was 0.006 ppm. which were still below the quality standards set by East Java Governor Regulation No. 10 year 2009 regarding ambient air quality standards and stationary source emissions in East Java, where the limits for H2S were 0.03 ppm and NH3 were 2.00 ppm. The response dose value (Rfc) for H2S was 0.002 mg/m3, and for NH3 it was 0.5 mg/m3. The RQ value for H2S was greater than 1, indicating a potential risk, while the RQ value for NH3 was less than or equal to 1, indicating safety for the community. H2S gas poses a risk, whereas NH3 does not pose a risk to the communities in the Benowo landfill environment. It is recommended that individuals have a healthy lifestyle, and wear masks in the Benowo landfill environment and local government should be able to carry out the risk management through related agencies to the people lived near Benowo landfill area.